Towards a Better Prediction of Cell Settling on Nanostructure Arrays—Simple Means to Complicated Ends. (15th April 2015) - Buch‐Månson, Nina; Bonde, Sara; Bolinsson, Jessica; Berthing, Trine; Nygård, Jesper; Martinez, Karen L.
Abstract : Vertical arrays of nanostructures (NSs) are emerging as promising platforms for probing and manipulating live mammalian cells. The broad range of applications requires different types of interfaces, but cell settling on NS arrays is not yet fully controlled and understood. Cells are both seen to deform completely into NS arrays and to stay suspended like tiny fakirs, which have hitherto been explained with differences in NS spacing or density. Here, a better understanding of this phenomenon is provided by using a model that takes into account the extreme membrane deformation needed for a cell to settle into a NS array. It is shown that, in addition to the NS density, cell settling depends strongly on the dimensions of the single NS, and that the settling can be predicted for a given NS array geometry. The predictive power of the model is confirmed by experiments and good agreement with cases from the literature. Furthermore, the influence of cell‐related parameters is evaluated theoretically and a generic method of tuning cell settling through surface coating is demonstrated experimentally. These findings allow a more rational design of NS arrays for the numerous exciting biological applications where the mode of cell settling is crucial. Abstract : Cell settling on nanostructure (NS) arrays is modeled and the effect of geometrical and cell‐related parameters is systematically evaluated. It is found that cell settling is highly dependent on both single‐NS dimensions and NS density, and predictive tools are developed for any NS array or cell type, thus allowing a rational design of future NS arrays for biological applications.